Serum DHEA and Testosterone Levels Associate Inversely With Coronary Artery Calcification in Elderly Men - Ohlsson Claes; Nethander Maria; Norlén Anna-Karin; Poutanen Matti; Gudmundsson Elias Freyr; Aspelund Thor; Sigurdsson Sigurdur; Ryberg Henrik; Gudnason Vilmundur; Tivesten Åsa (ENDOCRINE SOC, 2025)
Context Epidemiological and preclinical data support cardiovascular, mainly protective, effects of sex steroids in men, but the mechanisms underlying the cardiovascular actions of sex steroids are poorly understood. Vascular calcification parallels the development of atherosclerosis, but is increasingly recognized as a diversified, highly regulated process, which itself may have pathophysiological importance for clinical cardiovascular events.
Objective To investigate the association between serum sex steroids and coronary artery calcification (CAC) in elderly men.
Methods We used gas chromatography tandem mass spectrometry to analyze a comprehensive sex steroid profile, including levels of dehydroepiandrosterone (DHEA), androstenedione, estrone, testosterone, estradiol, and dihydrotestosterone, in men from the population-based AGES-Reykjavik study (n = 1287, mean 76 years). Further, sex hormone-binding globulin (SHBG) was assayed and bioavailable hormone levels calculated. CAC score was determined by computed tomography. The main outcome measures were cross-sectional associations between dehydroepiandrosterone, androstenedione, estrone, testosterone, dihydrotestosterone, and estradiol and quintiles of CAC.
Results Serum levels of DHEA, androstenedione, testosterone, dihydrotestosterone, and bioavailable testosterone showed significant inverse associations with CAC, while estrone, estradiol, bioavailable estradiol, and SHBG did not. DHEA, testosterone, and bioavailable testosterone remained associated with CAC after adjustment for traditional cardiovascular risk factors. In addition, our results support partially independent associations between adrenal-derived DHEA and testes-derived testosterone and CAC.
Conclusion Serum levels of DHEA and testosterone are inversely associated with CAC in elderly men, partially independently from each other. These results raise the question whether androgens from both the adrenals and the testes may contribute to male cardiovascular health.